Expectations and Interactions About Father Provision in South African, Black, Low-Income, Non-Resident Father Families - Nell, Erika; Lesch, Elmien (African studies (Johannesburg), 2025)
This study focuses on Black South African families and views the non-resident father as a member of a larger non-resident-father family system. Subsequently, rather than taking an individualistic approach that often blames fathers, father provision is approached as a family system issue. Informed by this approach, we individually interviewed four members of ten Black South African non-resident-father families about father involvement. Fathers' financial provision featured prominently in participants' accounts, and, in this article, we present two themes that shed light on this issue. The first theme illustrates how the various family members' privileging of fathers' financial contributions, rather than other contributions fathers could offer, led to discord and animosity between family members. The second theme, however, is encouraging, as it indicates that although all the participating family members prioritised financial provision, they also valued other father contributions. This emphasises the importance of continued efforts to challenge mainstream conceptions of fathers as primarily financial providers, and to encourage families to directly communicate expectations about non-resident-father provision and other forms of involvement.